All-electrical recursive generation and time-domain mode division multiplexing of Hermite–Gaussian pulses for optical, THz and RF links - Xiaonan Yu; Janosch Meier; Paulomi Mandal; Mohamed I. Hosni; Abhinand Venugopalan; Lingfei Wang; Thomas Schneider (Scientific Reports)
Abstract Space division multiplexing (SDM) with Hermite Gaussian (HG) modes, for instance, can significantly boost the transmission link capacity. However, SDM is not suitable in existing single mode fiber networks, and in long-distance wireless, microwave, THz or optical links, the far-field beam distribution may present a problem. Recently it has been demonstrated, that time domain HG modes can be employed to enhance the link capacity. However, implementing this method in wireless or fiber-based transmission systems is impractical due to the need for highly complex setups involving specialized lasers, wave shapers and other advanced devices. We propose a simple and fully electrical time-domain mode-division-multiplexing (TD-MDM) method based on the recursive generation of Hermite–Gaussian (HG) modes. It utilizes Gaussian pulse sequences, sawtooth signals, RF multipliers, adders, amplifiers, and Mach–Zehnder modulators for efficient multiplexing and demultiplexing. We show the time and bandwidth performance of 4 multiplexed orthogonal modes in transmitting 8 Gbps communication data (4 × 2 Gbit/s), demonstrating the feasibility of the recursive generation and multiplexing technique for TD-MDM with HG modes. The data rates were restricted by our experimental capabilities. With state-of-the-art equipment the method can easily be scaled to the terabit per second range.